Bearing Capacity Factor of Circular Footings on Two-layered Clay Soils - Benmoussa, Samir; Benmebarek, Sadok; Benmebarek, Naima (Civil Engineering Journal, 2021)
Geotechnical engineers often deal with layered foundation soils. In this case, the soil bearing capacity assessment using the conventional bearing capacity theory based on the upper layer properties introduces significant inaccuracies if the top layer thickness is comparable to the rigid footing width placed on the soil surface. Under undrained conditions the cohesion increases almost linearly with depth. A few theoretical studies have been proposed in the literature in order to incorporate the cohesion variation with depth in the computation of the ultimate bearing capacity of the strip and circular footings. Rigorous solutions to the problem of circular footings resting on layered clays with linear increase of cohesion do not appear to exist. In this paper, numerical computations using FLAC code are carried out to assess the vertical bearing capacity beneath rough rigid circular footing resting on two-layered clays of both homogeneous and linearly increasing shear strength profiles. The bearing capacity calculation results which depend on the top layer thickness, the two-layered clays strength ratio and the cohesion increase rates with depth are presented in both tables and graphs, and compared with previously published results available in the literature. The critical depth for circular footing is found significantly less than for strip footing.Â Doi: 10.28991/cej-2021-03091689 Full Text: PDF